Інтродукція маслинки багатоквіткової (Elaeagnus multiflora Thunb.) в Лісостепу України. Повідомлення 2. Насіннєве та вегетативне розмноження - Vasyuk, E.A.; Moroz, P.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The results of сherry elaeagnus (Elaeagnus multiflora Thunb.) breeding are done. It was found that for seed breeding it is better to use fresh seeds, which need stratification in two stages: 5 months at the temperature of +18...22 °С and 4 months at the temperature of +1...4 °С. The substratum was mixture of sand and peat (1:1). The ground germinating reached 91,0%. The best results were obtained under vegetative reproduction when half lignificated cuttings were used, optimum term for this method of propagation is the 2nd decade of June. Cuttings were treated by heteroauxin in concentration of 100 мg/l. In a mixture of sand, peat and turphy soil (1:1:1) 87% of cuttings took roots.